1941
DOI: 10.1002/jcp.1030170204
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigations on the respiration and diving of the florida manatee

Abstract: Besides the seals and cetaceans, the sea cows (Sirenia) may be said to represent the most marked adaptation to aquatic life of all mammals.A distinguishing feature of the sea cows is that they are the only forms of herbivorous mammals which are adapted exclusively to aquatic life. Compared with the great number and variety of seals and cetaceans the sca cows form a strikingly small order, comprising only the marine dugongs with three closely interrelated geographical races (Halicore dugong, Halicore hemprichi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
185
1

Year Published

1961
1961
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 159 publications
(198 citation statements)
references
References 5 publications
12
185
1
Order By: Relevance
“…In fact, some whales have weight-specific lung volumes much smaller than non-divers, such as man (Irving et al, 1941a;Scholander and Irving, 1941). This small lung volume may be an adapta tion to diving in animals which descend to great depths (Andersen, 1955), such as Sperm whales which have been found entangled in submarine cables A f npnfhc ov/on AyrooHi nn T 00.0 mof ore 1 Q!>7 ^ Mr 5/aa n anri Pav»!+nn (1977) have shown that beavers have a smaller lung volume/body weight ratio than man.…”
Section: Respiratory System and Metabolismmentioning
confidence: 99%
See 4 more Smart Citations
“…In fact, some whales have weight-specific lung volumes much smaller than non-divers, such as man (Irving et al, 1941a;Scholander and Irving, 1941). This small lung volume may be an adapta tion to diving in animals which descend to great depths (Andersen, 1955), such as Sperm whales which have been found entangled in submarine cables A f npnfhc ov/on AyrooHi nn T 00.0 mof ore 1 Q!>7 ^ Mr 5/aa n anri Pav»!+nn (1977) have shown that beavers have a smaller lung volume/body weight ratio than man.…”
Section: Respiratory System and Metabolismmentioning
confidence: 99%
“…T n Haon H 4 fko 1 « mnc rnlTançû X i iv~i nn H ccr on f a nri a i on f may become contained wholly within the respiratory dead space (Scholander» 1940). Of course, whether total lung collapse is possible or not depends on the size of the lungs relative to the size of the dead space.…”
Section: Respiratory System and Metabolismmentioning
confidence: 99%
See 3 more Smart Citations